Prediction of risk factors in hemodialysis patients with pulmonary hypertension: combined application of factorial and cluster analyses - Liu Xin-wu; Zeng Huan; Liao Bing-qing; Zhao Cheng-bo; Wang Run-xiu (Linchuang shenzangbing zazhi)
Objective To explore the risk factors of pulmonary hypertension（PH）in hemodialysis.Methods Retrospective analysis was performed for clinical data of 91 patients with hemodialysis PH.And factorial and cluster analyses were conducted for examining the risk factors of PH in hemodialysis.Results Eleven unrelated common factors were extracted from 15 parameters by factor analysis.These 11 common factors represented 90.32% of the information of original parameters.After rotation, it could reflect age, gender, anemic status, protein metabolism, lipid metabolism, renal function, inflammation & fibrinolysis status, nutritional status and parathyroid hormone level, etc.And then the results were divided into four categories by cluster analysis: male aged under 60 years, male aged above 60 years, female aged under 60 years and female aged above 60 years.There were varying degrees of anemia, plasma fibrinogen was higher in different degrees, males were significantly more than females and the number of patients aged above 60 years increased significantly.At the same time, the levels of ferritin, blood phosphorus and parathyroid hormone were higher in most patients in categories 2/3/4.Conclusions Anemia and high plasma fibrinogen are important factors in PH patients on hemodialysis.Age and gender may be risk factors.Ferritin, blood phosphorus and parathyroid hormone are potential risk factors in patients with hemodialysis PH.